Ten political ideas that have shaped the modern world - Lakoff, Sanford A. (Rowman & Littlefield Publishers, 2011)
At a time when political labels are hurled carelessly in the public square, Sanford Lakoff provides a careful and highly accessible introduction to ten political ideas that have shaped modern thinking. Each chapter traces the history and examines the meaning of one of these ideas, clarifying its meaning and impact by examining its history and interpretation. By explaining what these ideas have come to mean, both those we may endorse and those we may deplore, Lakoff challenges readers' preconceptions and promotes critical thinking about the big questions of politics. The result will appeal to a.